2016
DOI: 10.1155/2016/1067506
|View full text |Cite
|
Sign up to set email alerts
|

Active Magnetic Bearings Stiffness and Damping Identification from Frequency Characteristics of Control System

Abstract: At present, the stiffness and damping identification for active magnetic bearings (AMBs) are still in the stage of theoretical analysis. The theoretical analysis indicates that if the mechanical structure and system parameters are determined, AMBs stiffness and damping are only related to frequency characteristic of control system, ignoring operating condition. More importantly, few verification methods are proposed. Considering the shortcomings of the theoretical identification, this paper obtains these coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…A method with multi-frequency excitation for measurement of equivalent stiffness and damping of the active magnetic bearing rotor was presented [7]. From the unbalance response [8,9] and frequency characteristics [10], similar kinds of magnetic bearing parameter identification approaches were found. For ball bearing systems, the parameters were identified with simulated and experimental data [11].…”
Section: Introductionmentioning
confidence: 99%
“…A method with multi-frequency excitation for measurement of equivalent stiffness and damping of the active magnetic bearing rotor was presented [7]. From the unbalance response [8,9] and frequency characteristics [10], similar kinds of magnetic bearing parameter identification approaches were found. For ball bearing systems, the parameters were identified with simulated and experimental data [11].…”
Section: Introductionmentioning
confidence: 99%
“…A method with multi-frequency excitation for measurement of equivalent stiffness and damping of active magnetic bearing rotor was presented by Jiang et al [10]. Based on the unbalance response [11,12] and frequency characteristics [13], similar kinds of magnetic bearing parameter identification approaches were presented. Likewise for ball bearing systems, the parameters were identified with simulated and experimental data [14].…”
Section: Introductionmentioning
confidence: 99%
“…The robustness and performance of the proposed method were checked against several measurement errors. AMB was used as an exciter to generate the force response data which were further used to develop an algorithm to evaluate the AMB dynamic parameters, both theoretically and experimentally [13]. A methodology was suggested that utilizes the unbalance response of the AMB integrated rotor to estimate the AMB closed-loop characteristic parameters [14].…”
Section: Introductionmentioning
confidence: 99%